Возможности Беларуси в создании автоматической измерительной информационной системы раннего оповещения в речных бассейнах - Rogunovich В. (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2010)
The quantity of extreme situations in Belarus hydrosphere is being increased bringing a lot of trouble: destroyed buildings and culture monuments, human death, etc. The function between early information term and the damage decrease is established: in 1 hour – (0,5-0,8) %, in 1 day – (12-15) %, in 2 day – (25-30) %. To reduce this damage the systems of early information are called. The devices for mathematic models of river systems and water flowing with admixture transportation processes creation as well as the automatic devices for quantity and quality water characteristics measuring are proposed and systemized by the author premising to automatic measuring systems of early information creation.